Challenges of managing hypertension in Pakistan - a review - Adil Elahi; Arzina Aziz Ali; Aamir Hameed Khan; Zainab Samad; Hunaina Shahab; Namra Aziz; Aysha Almas (BMC, 2023)
Abstract Background This review aims to describe existing evidence on the state of hypertension in Pakistan, including the prevalence, associated risk factors, preventive strategies, and challenges in the management of hypertension. Methods A comprehensive literature search was conducted electronically using PubMed and Google Scholar. Using specific screening methodology, 55 articles were selected to be included. Results We found from this extensive review that several small studies report high prevalence of hypertension but there is a lack of population based prevalence of hypertension in Pakistan. Lifestyle risk factors such as obesity, unhealthy diet, decreased physical activity, low socioeconomic status, and lack of access to care were the main associated factors with hypertension. Lack of blood pressure monitoring practices and medication non-adherence were also linked to uncontrolled hypertension in Pakistan and were more evident in primary care setups. The evidence presented is essential for delineating the burden of the disease, hence allowing for better management of this underserved population. Conclusion There is a need for updated surveys to depict the true prevalence and management of hypertension in Pakistan. Cost-effective implementation strategies and policies at the national level are needed for both prevention and control of hypertension.